Functional Dyspepsia and Chronic Gastritis: Similarities and Differences - S.M. Tkach (Gastroenterologìa, 2014)
The article deals with is one of the most common symptoms, faced by general practitioners or gastroenterologists — functional dyspepsia. Its clinical manifestations are described, attention is paid to the treatment issues. It is emphasized that the primary treatment of functional dyspepsia in most cases is an empirical, based on clinical assessment of predominance of acid-dependent or dysmotor symptoms, for which proton pump inhibitors, prokinetics, or combination drugs containing proton pump inhibitors and prokinetics, such as Omez D or Omez DCR, are administered, respectively.